1980
DOI: 10.1073/pnas.77.11.6922
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of in vitro myogenesis on a trophic protein present in chicken embryo extract.

Abstract: A trophic protein (sciatin) purified from sciatic nerves has been shown to enhance the morphological develop ment and to promote the maintenance of sletal muscle cells in vitro Proc. NatL Acad.Sci. USA 76,2470-24741. We have elicited a specific antiserum against purified sciatin in rabbits. By using this antiserum, we have examined whether sciatin is also required for the initial differentiation of avian myogenic cells in vitro. Sciatin was found to be a component of chicken embryo extract, a constituent of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Chicken transferrin has been found to be necessary for the normal growth and differentiation of chick embryo muscle cells in culture. It was first shown that chick embryo extract was an absolute requirement for myogenesis in vitro (Oh and Markelonis, 1980;Hagiwara, Kimura, and Ozawa, 1981;Ii, Kimura, and Ozawa, 1982) and that its trophic effects could be replaced by a small amount of embryonic or adult chicken serum Ozawa and Kohama, 1978), extracts of adult chicken muscle Matsuda, Spector, and Strohman, 19841, extracts of adult chicken neural tissues (Markelonis et al, 1982;Popiela, Ellis, and Festoff, 19821, and also microgram quantities of purified chicken transferrin (Kimura, Hasegawa, and Ozawa, 1982;Saito et al, 1982). This muscle trophic factor was now been isolated and identified as Tf-Fez .…”
Section: Discussionmentioning
confidence: 99%
“…Chicken transferrin has been found to be necessary for the normal growth and differentiation of chick embryo muscle cells in culture. It was first shown that chick embryo extract was an absolute requirement for myogenesis in vitro (Oh and Markelonis, 1980;Hagiwara, Kimura, and Ozawa, 1981;Ii, Kimura, and Ozawa, 1982) and that its trophic effects could be replaced by a small amount of embryonic or adult chicken serum Ozawa and Kohama, 1978), extracts of adult chicken muscle Matsuda, Spector, and Strohman, 19841, extracts of adult chicken neural tissues (Markelonis et al, 1982;Popiela, Ellis, and Festoff, 19821, and also microgram quantities of purified chicken transferrin (Kimura, Hasegawa, and Ozawa, 1982;Saito et al, 1982). This muscle trophic factor was now been isolated and identified as Tf-Fez .…”
Section: Discussionmentioning
confidence: 99%
“…Transferrin is thus a molecularly defined effector in this model system. It was recently shown that the "muscle trophic factor" required for myogenesis (38) is identical to transferrin (39,40). Evidence from these two developmental systems therefore suggests that transferrin is an important serum factor for organogenesis.…”
mentioning
confidence: 99%
“…An alternative explanation is that some neurotrophic effect of the spinal cord is important in the organotypic cultures. Adult myosins were not seen in cultures grown in medium containing chicken embryo extract [I, 2, 281 which contains some nerve-derived components [16]. Such medium additives may not substitute for the actual presence of the cord, however, because the necessary factors are labile, become too dilute, or may need to be applied topically by the axon terminals.…”
Section: Histochemical ( a X ) And Immunocytochemical (Wf) Reactionmentioning
confidence: 99%